Copper and very low birthweight babies. Issue 1 (January 1988) - Soo, T L; Simmer, K; Carlson, L; McDonald, L
Abstract : Serum concentrations of copper and ceruloplasmin were measured in 24 very low birthweight babies. They were high in those weighing less than 1000 g, and critically ill or receiving intravenous nutrition, and normal in those with bone disease, neutropenia, or oedema. Care is needed to maintain adequate concentrations without toxicity.